THE MECHANISM OF MOISTURE EXCHANGE OF FRUITS AND VEGETABLES WITH THE AMBIENT AIR - N. G. Scheglov; O. A. Maklichenko (Современная наука и инновации)
The increased losses of raw material during storage of fruits and vegetables are the main cause of the seasonal nature of many processing enterprises, but also they greatly affect their cost in the process of implementation. The numerous data for the determination of mass loss of raw materials shows that the largest share consists of loss from respiration and evaporative losses of moisture that reach 10-12 % or more depending on the material type and the duration of storage. The authors make an attempt based on the molecular representations of the laws of physics to describe the process of diffusion of molecules oxen through the epidermis and to identify the main regularities of mass transfer fi included in equation Dalton. An analytical expression for determining the coefficient of mass transfer for fruits and vegetables, stored in the refrigeration chambers, was obtained